Simulação numérica de correntes de densidade em configuração não-confinada com alimentação contínua - Ruschel, Karina (2022)
Density currents are flows where the moviment between the fluids starts because of specific mass differences due to gravitational forces. When specific mass differences are caused by suspended particles, they are called turbidity currents. They can be responsible for the generation of alluvial fans, cliffs and porous rocks, which can become hydrocarbon reservoirs. The main objective of this study is to identify which parameters are used in the modeling of density currents that define their propagation form in hyperpycnal currents in a channel-basin configuration, with continuous flow, in conservative and non-conservative flows. The entrance condition of the domain, to approximate to natural characteristics of the river bottom, are used parabolic profiles comparing the effect with square entrance. In this study, the effect of tilting on the bed was also considered by applying solid rotation. The equations that govern the system are the Navier-Stokes and scalar transport equations. From these mathematical models and using the code Incompact3d, fourteen numerical simulations were performed using ILES methodology to determine the mesh, numerical dissipation and time step criteria. Afterwards, six simulations were studied and evaluated for code validation with reference experiments, where they presented variations in relation to the front position between 0% and 14.22%. From these findings, seven simulations were proposed to study the results in the front position, lateral position, aspect ratio, current propagation velocity and the relationship of dimensionless parameters with the current front. It is concluded that the slope of the reservoir bottom may be responsible for making the current reach more distal positions and less lateral scattering. The consequence of a parabolic input geometry is also responsible for the lower current scattering. The results of the simulations considering suspended particles show that these are responsible for the change in the shape of the current, as well as the increase in the falling speed alters the shape of the deposit.